Application of the Logical Matrix Approach in Strategic Management - Trocki, Michał; Bukłaha, Emil; Juchniewicz, Mateusz; Metelski, Witalij (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The main goal of the article is to show the issues of strategy implementation as an area of activity at the border of both strategic management and project management. The authors try to explain why the implementation of the strategy is associated with an invariably high level of difficulty and identify a number of factors contributing to this state. They show that one of the biggest obstacles to successful strategy implementation is the lack of appropriate implementation tools. This is the basis of the main goal of the article, which is the presentation of the Logical Matrix (LFA) approach as a concept of increasing the effectiveness of implementing strategic goals by consistently combining the phase of strategic analysis and planning with the phase of their implementation. A detailed description of the LFA concept from the above point of view is the main part of the article.The article uses primarily literature research (desk research) of Polish and foreign professional publications in the above field.